Schuhputzer = Sciuscià - Cicognini, Alessandro (Pidax Film, 2019)
The story of two Roman orphans abused by the state reform system.
Bonumsmaterial: Booklet. Timeless Cinema - Eine Dokumentation über Vittorio de Sica & Gespräche über de Sica
Bildformat: 4:3
Orig.: Italien 1946
Keywords: Abused children -- Italy -- Rome -- Drama; Feature films; Foreign films; Motion pictures, Italian; Orphans -- Italy -- Rome -- Drama; Italien; Rom; Film; DVD-Video